Ristocetin- and Thrombin-induced Platelet Aggregation at Physiological Shear Rates: Differential Roles for GPIb and GPIIb-IIIa Receptor - Kasirer-Friede, A.; Frojmovic, M. M. (Thrombosis and Haemostasis, 1998)
We recently reported that washed platelets (WP) activated with ADP and expressing surface-bound vWF aggregated in flow through small tubes or in a cylindrical couette device at physiological shear rates of G = 300 s–1-1000 s–1 in the absence of exogenous ligands, with GPIb-vWF partially, and activated GPIIb-IIIa totally required for the aggregation. We have now extended these studies to aggregation of platelets “activated” with ristocetin or thrombin. Washed platelet suspensions with added soluble vWF and ristocetin (0.3-0.75 mg/ml), or activated with thrombin (0.01-0.5 U/ml) but no added ligand, were sheared in a coaxial cylinder device at uniform shear rate, G = 1000 s–1. The collision capture efficiency (αG) with which small aggregates form (= experimental/calculated initial rates of aggregation) was correlated with vWF platelet binding assessed by flow cytometry. The vWF-GPIb interaction was exclusively able to support ristocetin-mediated shear aggregation of metabolically active platelets, with very few vWF monomer equivalents bound per platelet (representing ≤10 molecules of 10 million Da) required to yield high capture efficiencies (αG = 0.38 ± .02; n = 11), suggesting rapid and stable bond formations between vWF and GPIb. However, platelet surface-expressed vWF, generated by addition of thrombin to washed platelets, was found to mediate platelet aggregation with αG = 0.08 ± .01 (n = 6), surprisingly comparable to that previously reported for WP and ADP activation. Blocking the GPIIb-IIIa receptor decreased αG by 95 ± 3% (n = 3), while a monoclonal antibody to the vWF site on GPIb caused a 49 ± 7% (n = 8) decrease in αG. The partial role for GPIb thus appears to reflect a facilitative function for increasing contact time between flowing platelets, and allowing engagement of the GPIIb-IIIa receptor to yield stable attachment.